Structure, Composition, and Environmental Conditions of Rehabilitated Mangrove Forests in Kupang Bay, Indonesia - Jeriels Matatula; Meilyn Renny Pathibang (Green Insight Solutions, 2026)
Mangrove rehabilitation is widely implemented to restore degraded coastal ecosystems; however, post-restoration stand development and its environmental controls remain insufficiently understood. This study assessed species composition, stand structure, diversity, and environmental drivers of growth in rehabilitated mangrove forests on the northern coast of Kupang Bay, Indonesia. Vegetation data were collected using systematic sampling across nine permanent plots, covering growth stages from seedlings to trees, and analyzed using the importance value index (IVI), Shannon-Wiener diversity index (H'), and species richness index. Environmental variables, including salinity, mud thickness, pH, and slope, were measured to evaluate their influence on mangrove growth using multiple linear regression. A total of eight mangrove species were identified, with Avicennia marina dominating at the seedling stage (IVI 123.48%) and Sonneratia alba dominating at the sapling (IVI 93.86%), pole (IVI 146.83%), and tree stages (IVI 104.10%). Overall species diversity was moderate (H′ = 1.16), while species richness was low, indicating limited compositional complexity despite successful establishment. Environmental conditions were within suitable ranges for mangrove growth, with a mean salinity of 28.68 ppt, pH 7.19, mud thickness 71.97 cm, and slope 2.08%. Regression analysis showed that environmental variables explained 51% of the variation in growth (R² = 0.51), with mud thickness and pH exerting significant positive effects, whereas salinity and slope were not significant predictors. These findings demonstrate that rehabilitated mangrove forests can achieve structurally stable communities under favorable environmental conditions; however, species diversity remains constrained. The results highlight the importance of substrate characteristics and soil chemistry in shaping restoration outcomes and provide critical insights for improving mangrove management and rehabilitation strategies in tropical coastal ecosystems.